2012
DOI: 10.1093/eurjhf/hfs002
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass loss in chronic heart failure is associated with secondary hyperparathyroidism and has prognostic significance

Abstract: AimsChronic heart failure (CHF) is associated with increased risk of osteoporosis. We investigated the relationship between severity of CHF and bone loss, underlying pathophysiological mechanisms, and the prognostic significance of bone mass changes in heart failure. Methods and resultsTotal body (TB) and femoral (F) bone mineral density (BMD), and T-and Z-scores in the femur were measured in 60 men with CHF (56 + 11 years) and 13 age-matched men free from CHF. The composite study endpoint was death, implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 34 publications
3
44
0
6
Order By: Relevance
“…The latter is possible because hyperaldosteronism also has been shown to cause bone loss in rodents (29,30). Osteoporosis also is widely recognized as being associated with heart failure, particularly in elderly patients (31); the proposed pathophysiological mechanisms include secondary hyperparathyroidism, testosterone deficiency, and excessive inflammatory cytokine production (31)(32)(33). Nonetheless, inappropriate AVP secretion is also a hallmark of low-output cardiac failure and in these instances may contribute to bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is possible because hyperaldosteronism also has been shown to cause bone loss in rodents (29,30). Osteoporosis also is widely recognized as being associated with heart failure, particularly in elderly patients (31); the proposed pathophysiological mechanisms include secondary hyperparathyroidism, testosterone deficiency, and excessive inflammatory cytokine production (31)(32)(33). Nonetheless, inappropriate AVP secretion is also a hallmark of low-output cardiac failure and in these instances may contribute to bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…3,4, 23 Recent clinical studies have suggested that secondary hyperparathyroidism is associated with HF severity, increased pulmonary capillary wedge pressure, increased BNP, decreased LVEF, and decreased cardiac index in patients with HF and that it develops as a compensatory response to HF. 5,6,9,10, 24 More recent studies have reported that higher PTH in the steady state is associated with higher all-cause and cardiovascular mortality risk 8,10,25-28 and a higher risk of hospitalization for HF. 9, 29 In the present study, approximately 60% of patients had abnormal increase in serum PTH (>65 pg/ml) and impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…271 Low vitamin D and elevated parathyroid hormone levels appear to be associated with CHD. [272][273][274] It is well established that adults with advanced heart failure have lower bone mass and vitamin D levels, 244 with approximately half of patients with severe heart failure having osteopenia or osteoporosis, so it is of concern that a significant number of patients with complex CHD at such a young age have demonstrated markers of abnormal bone density/function because this may be a harbinger of osteopenia, osteoporosis, and fracture risk later in life. Patients with Down syndrome are at increased risk for low bone mineral density and fractures.…”
Section: Calcium Hemostasis and Bone Healthmentioning
confidence: 99%